Statistical Data Processing Training to Support Final Assignments with E-Views 10 for FEB UNIKI Bireuen Students - Kamaruddin, Kamaruddin; Azhari, Azhari; Yanna, Sri; Ibrahim, Ibrahim; Afriana, Afriana; Abqa, Rizkan (LPPM Umuslim, 2025)
The difficulty that makes students take a long time to complete their final assignment in the form of a thesis is when processing data. Moreover, the majority conduct quantitative research that requires statistical data processing with the help of certain software. So it is not uncommon for them to use consultants or paid assistance for this. So the training carried out by lecturers in community service by introducing E-Views 10 software, aims to help students - to be able to process data and data analysis techniques independently with the E-Views 10 program and be able to make decisions in analyzing research results and discussions. This training was attended by 15 participants, with strategies or stages, starting with providing materials, discussions and direct practice. During the practice, mentoring was carried out by 5 (five) speakers as mentors.